2014
DOI: 10.1177/1073191114534959
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Schedule for Nonadaptive and Adaptive Personality Brief Self-Description Rating Form (SNAP-BSRF)

Abstract: The Schedule for Nonadaptive and Adaptive Personality full-length (SNAP) and short versions (SNAP-SRF and SNAP-ORF) were developed as measures of normal-range and more pathological personality traits. This study investigated the validity of the SNAP Brief Self-Description Rating Form (SNAP-BSRF), an alternative version of the SNAP Self-Description Rating Form (SNAP-SRF) revised for further brevity. The scales of the SNAP-BSRF showed good convergence with the SNAP-SRF and the SNAP Other-Description Rating Form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 71 publications
(127 reference statements)
2
2
0
Order By: Relevance
“…Except for Mistrust, we did not observe significant associations between self‐ and informant‐reported SNAP traits. This is consistent with previous findings demonstrating low agreement between self‐ and informant‐reported personality (Harlan & Clark, 1999; Kotelnikova et al, 2015; Ready et al, 2002). In addition, self‐reported caregiver SNAP traits were unrelated to their parenting.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Except for Mistrust, we did not observe significant associations between self‐ and informant‐reported SNAP traits. This is consistent with previous findings demonstrating low agreement between self‐ and informant‐reported personality (Harlan & Clark, 1999; Kotelnikova et al, 2015; Ready et al, 2002). In addition, self‐reported caregiver SNAP traits were unrelated to their parenting.…”
Section: Resultssupporting
confidence: 92%
“…As we were interested in interpersonal traits that may be related to hostile and responsive parenting, self‐ and informant‐reported subscales assessing the following traits were included in this study: Aggression (two items; α self = .31; α informant = .45; AIC self = .18; AIC informant = .29; SB self = .31; SB informant = .45; e.g., easy to lose temper and hold on to anger vs. does not lose temper easily and quick to forgive and forget), negative temperament (NT; three items; α self = .77; α informant = .79; AIC self = .53; AIC informant = .56; e.g., moody and emotionally labile vs. even‐tempered) and mistrust (two items; α self = .61; α informant = .69; AIC self = .44; AIC informant = .53; SB self = .62; SB informant = .69; e.g., seldom trust others and expect to be let down by others vs. trust easily). Our reliability coefficients are generally similar to those reported by Harlan and Clark (1999) and others (Kotelnikova, Clark, Vernon, & Hayden, 2015; Ready & Clark, 2002; Ready, Watson, & Clark, 2002; Schalet, Durbin, & Revelle, 2011), except for self‐reported aggression, which was relatively low (although all internal consistency values are within the expected range for scales with only two or three items). We provide average interitem correlations (AIC) as indices of the scales' internal consistency independent of scale length (Clark & Watson, 2019), as well as the Spearman‐Brown (SB) statistic for the aggression and mistrust scales, another reliability index recommended for two‐item scales (Eisinga, Te Grotenhuis, & Pelzer, 2013).…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…The results of CFA for the model showed that χ 2 = 90.27, df = 58, χ 2 / df = 1.56, Bollen–Stine bootstrap, p = .192, GFI = 0.90, AGFI = 0.84, and RMSEA = 0.07. The values of GFI, AGFI, and RMSEA were considered acceptable (Anestis, Gottfried, & Joiner, 2015; Cohen & Williamson, 1988; Hair et al, 1998; Kotelnikova, Clark, Vernon, & Hayden, 2015; Nixon & Oscar, 1989). Thus, the four-factor model was confirmed by the CFA (Figure 2).…”
Section: Resultsmentioning
confidence: 99%